Исследование технологичекого процесса холодного выдавливания ступенчатых валов - Кузьменко, Виктор Иванович; Зальвовский, Александр Юрьевич; Таки, Ахмед (НТУ "ХПИ", 2015)
Работа посвящена исследованию процессов штамповки ступенчатых валов редуцированием и высадкой с учетом возможной потери устойчивости высаживаемой заготовки, а также валов с эксцентриками путем использования прогрессивных методов обработки металлов давлением. Предложены и рассмотрены возможные варианты техпроцессов холодного выдавливания и высадки со сдвигом (изгибом) для получения заготовки эксцентрикового вала тормозной системы автотракторной техники. Описаны результаты исследований, полученные с помощью метода конечных элементов (МКЭ).

The work is devoted to research the processes of stamping stepped shafts reduction and landing, taking into account the possible loss of stability to plant harvesting, as well as eccentric shafts through the use of advanced methods of metal forming. Proposed and discussed options for technological processes of cold extrusion and drop-off shift (bending) to produce billets eccentric shaft brake automotive engineering. The results of research obtained by using the finite element method (FEM). Investigations have shown that in case of exceeding admissible values planted portion of the blank may form a defect in the form of a clamp on the generatrix of the eccentric, there is a delay of the burr in the upper part of the eccentric, there is a clip on the back side surface of the cam, and also has a significant increase deforming force, with good quality product. To determine the relative length of the workpiece and planted stroke displacement determine the most appropriate option that requires additional research using experimental design.
The study of the process of cold extrusion stepped shafts
Keywords: вал эксцентриковый; высадка; макроструктура; метод конечных элементов; eccentric shaft; heading; macrostructure; finite element method